EVALUASI KINERJA MENGAJAR GURU KELAS V BERSERTIFIKASI DI DAERAH BINAAN 2 KECAMATAN PARAKAN - Tambah Setyowati; Bambang Suteng Sulasmono (Universitas Kristen Satya Wacana, 2015)
This research has three main objectives : (1) to evaluate the teachers in planning the lesson; (2) to evaluate the teachers in class; (2) to evaluate the teachers in grading the study’s result. This research conducted in Target areas 2 Districts Parakan in second semester of 2014/2015 which subject is the certified teachers in nine elementary schools in Parakan. This research is an evaluated research based on mix method. The data was gained by observation, interview, document, and survey. The result showed that 88.89% certified teachers in Parakan had a good record in teaching and 11.11% were in a very good phase even in the planning, teaching, or the evaluating. Though there are some aspect that need to be fixed such as : (1) planning the chosen study’s medium and source (2) implementing the ICT (3) conducting contextual lesson; (3) the selection ofmethod; and (4) the questions to evaluate the study.